POLYGENIC RISK PROFILING OF CANDIDATE GENE POLYMORPHISMS AS EARLY PREDICTORS OF ACUTE PANCREATITIS SEVERITY IN AN UZBEK COHORT (Symposium on Natural and Applied Sciences, 2026)
Severe and necrotizing acute pancreatitis (AP) develops in approximately 15-20% of all cases and carries a mortality of up to 40% when pancreatic necrosis becomes infected [1]. Standard severity scoring systems, including BISAP, APACHE II and the Revised Atlanta Classification [2], are calibrated to clinical data collected at 48-72 hours - a window that frequently exceeds the optimal moment for surgical intervention. This inherent delay is particularly consequential in Central Asian emergency centres, where late hospital presentation further compresses the time available for risk stratification. Genetic variation in pathways governing vascular repair (VEGFA), extracellular matrix remodelling (MMP9), antioxidant defence (CAT), trypsin inhibition (SPINK1) and hepatic drug metabolism (CYP2C19) has been associated with susceptibility to pancreatic necrosis in European and East Asian populations, yet virtually no data exist for Central Asian cohorts [3]. Given that allele frequencies differ markedly across ethnic groups, direct extrapolation of foreign risk estimates to clinical practice in Uzbekistan is methodologically unsound.